초기 조건이 부유식 풍력터빈 동역학 해석의 과도응답에 미치는 영향 - 송진섭(Jin-Seop Song); 임채환(Chae-Whan Rim); 문석준(Seok-Jun Moon); 남용윤(Yong-Yun Nam) (Han-guk haeyang gonghak hoeji (Online), 2014)
The IEC standard for onshore or offshore wind turbines requires additional dummy simulations (at least 5 s) for the transient responses due to initial conditions. An increase in the dummy time causes a considerable increase in the computational cost considering multiple design spirals with several thousand design load analysis cases. A time of 30 s is typically used in practical simulations for a wind turbine design with a fixed platform. However, 30 s may be insufficient for floating offshore wind turbines (FOWT) because the platforms have lower natural frequencies, and the transient responses will last much longer. In this paper, an initial condition application algorithm is implemented for WindHydro, and the appropriate dummy simulation time is investigated based on a series of dynamic simulations of a FOWT. As a result, it is found that more than 300 s is required for the platform to have stationary motion after the initial transient responses for the FOWT under the conditions considered.